2020
DOI: 10.1371/journal.pone.0232128
|View full text |Cite
|
Sign up to set email alerts
|

The engaging nature of interactive gestures

Abstract: The social interactions that we experience from early infancy often involve actions that are not strictly instrumental but engage the recipient by eliciting a (complementary) response. Interactive gestures may have privileged access to our perceptual and motor systems either because of their intrinsically engaging nature or as a result of extensive social learning. We compared these two hypotheses in a series of behavioral experiments by presenting individuals with interactive gestures that call for motor resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 56 publications
1
6
0
1
Order By: Relevance
“…We used G*Power 3.1.9.2 programme to calculate our target sample size (Faul et al, 2007). The target sample size was estimated as 66 when we set the effect size as .20 based on the previous research (Curioni et al, 2020). Our sample consisted of 66 undergraduate and graduate students who were native Turkish speakers ( M age = 21.05, SD age = 1.67, 60 female).…”
Section: Methodsmentioning
confidence: 99%
“…We used G*Power 3.1.9.2 programme to calculate our target sample size (Faul et al, 2007). The target sample size was estimated as 66 when we set the effect size as .20 based on the previous research (Curioni et al, 2020). Our sample consisted of 66 undergraduate and graduate students who were native Turkish speakers ( M age = 21.05, SD age = 1.67, 60 female).…”
Section: Methodsmentioning
confidence: 99%
“…Los gestos se integran dentro de un proceso de relación social, en el cual, el empleo de los signos no verbales hacen parte de la interacción, las relaciones y los vínculos con los demás, la organización y en general con el control de la comunicación, la cual está cargada de un alto valor sociocultural que agrega información al mensaje transmitido (Alibali y Kita, 2010;Cestero, 2015, Curioni et al, 2020Fossa, 2019;Goldin-Meadow, 2005;Özçalışkan et al, 2016;Waters y Beck, 2015). Ahora bien, los gestos se pueden clasificar en: emblemas, ilustradores, reguladores, adaptadores y señales de afecto (Knapp y Hall, 2009), en este sentido, estos fueron los aspectos abordados en el presente estudio.…”
Section: Porras Et Alunclassified
“…One critical difference distinguishing social affordances from object affordances is that, during social interactions, one is required to reciprocate the other individual's action (e.g., extending their right hand for a handshake) not with the spatially compatible response (the left hand), but the hand that complements (the right hand) the interaction partner's action. Curioni et al (2020) used images of individuals performing either interactive (e.g., handshake) or communicative (e.g., thumbs up) gestures with either the right hand, which was located in the left side of the screen since the body of the individual was centered, or the left hand, which was located in the right side of the screen. The spatial compatibility effect that resulted from the location of the gesture hand in the screen was found to be lower in the communicative than in the interactive gesture condition, which indicated that interactive gestures led to a slight facilitation of the spatially incompatible, but the affordance-compatible hand.…”
Section: Introductionmentioning
confidence: 99%
“…They revealed that although both stimulus types produced strong spatial compatibility effects, the directional compatibility effect, which was in line with social affordances, occurred only for the handshake gestures. It is important to note that the type of response administration might be a critical factor in the emergence of the social affordance effect, since faster complementary hand responses were observed in studies using key release as responses (Faber et al, 2016;Farmer et al, 2021;Flach et al, 2010;Liepelt et al, 2010), whereas the only study that used keypress responses reported the opposite pattern, showing faster responses for the spatially compatible, but affordance-incompatible hand responses (Curioni et al, 2020).…”
Section: Introductionmentioning
confidence: 99%